Smallholder farmers’ perception on the environmental impact of eucalyptus plantations: The case of the upper Blue Nile basin of Ethiopia - Abdurohman Yimam; Asnake Mekuriaw; Dessie Assefa; Woldeamlak Bewket (Sustainable Futures)
In Ethiopia’s northern highlands, Eucalyptus species are increasingly favored by smallholder farmers due to their fast growth and economic returns. However, the rapid expansion of monoculture Eucalyptus plantations has raised environmental concerns. This study investigates smallholder farmers’ perceptions of the ecological impacts of Eucalyptus and the key factors driving its adoption on farmland. A total of 350 farmers were selected through multistage sampling from three purposively chosen Kebeles. Data were collected via household surveys, six key informant interviews, and three focus group discussions. A binary logit model was used to analyze the quantitative data, supported by checks for multicollinearity and reliability of Likert-scale responses. Results indicate that while farmers benefit economically, many recognize negative environmental effects, including soil nutrient depletion, water source drying, reduced undergrowth regeneration, and competition with nearby crops and pastures. At the same time, 80 % of respondents noted that Eucalyptus reduces pressure on natural forests, and 76 % acknowledged its role in providing wildlife habitat. The adoption of Eucalyptus was significantly influenced positively by off-farm income (P < 0.01) and land size (P < 0.05), and negatively by family size (P < 0.01), road distance (P < 0.001), and land ownership (P < 0.05). The study highlights the need for balanced land use strategies that consider both environmental sustainability and rural livelihoods.